THE IMPLEMENTATION OF PERPETUAL LISTING SYSTEMS FOR THE FINANCIAL REPORTING OF FINANCIAL COMPANIES - Ela Revita 1, Maria Lapriska Dian; 2, Annisa (Universitas Kristen Indonesia, 2018)
Current technological developments have pushed people into the era of information globalization. Information is very important, every company apply accounting as a tool of information. Classically accounting is the process of recording, grouping, summarizing, and reporting of transactions that occur in the company. The process is part of the accounting cycle that will produce financial statements. The Financial Statement is the Information used by Management for decision making. Recording of inventory is one activity activity that distinguishes a trading company with a service company, so that inventory recording is important in a trading company. Therefore, at the time of recording the purchase or sales transactions to produce the Financial Statement, it is necessary to determine the application of inventory recording method, either perpetually or periodically is necessary at the time of making the Financial Statement of the trading company, as it affects the journal creation of the transaction, either the purchase transaction as well as merchandise sales. The research was conducted at PT Sinar Kharisma Mitra Agung, a trading company located in bekasi, providing the best quality products, serving one stop shopping or one place purchasing service for all insulation, wire mesh, faoundry and refracory materials to customers. The results of research conducted by the company need to apply perpetual recording system, so the company can know the amount of goods inventory easily, and quickly and minimize losses caused by loss of merchandise. This needs to be done so that the company can provide products with the best quality on time, in accordance with the vision and mission of the company, which always committed with reliable stock and delivery, so as to provide the best service support and able to offer competitive prices to customers..Keywords: Perpetual Listing System, Financial Report, Merchandising Company